AGRARIAN SECTOR OF ECONOMY OF KAZAKHSTAN - K.M. Utepkaliyeva,; B.M. Dyusgaliyeva,; A.D. Mukasheva,,; A.M. Kalauov, (Academic Journal of Physical and Chemical Sciences, 2019)
According to the authors, the agricultural sector is a collection of sectors of the national economy engaged in the production of agricultural products, their storage, processing and bringing to the consumer. The development of the agricultural sector contributes to a more rational allocation of production, an integrated and efficient use of resources, improvement of the final results of its operation, and ensuring the country's food security. In developed countries, the agro industrial complex accounts for a significant part of workers, fixed and circulating capital, and GDP. It is on the scale of the agro-industrial complex, the perfection of its structure and the efficiency of its functioning that the increase in the standard of living of the population and the provision of food security in general largely depend. The economy of Kazakhstan is characterized by the globalization of economic relations, increasing competition in the market. Domestic experience shows that reforms in the agricultural sector are carried out with considerable difficulties. To a greater extent, this is connected with the complex processes of transformation of ownership forms in the countryside and the formation of a class of real owners, as well as their adaptation to market mechanisms of free pricing and liberalization of foreign trade.